ATTITUDE TOWARDS MODERN CONTRACEPTIVES AMONG SINGLE WOMEN IN UNIVERSITIES IN KWARA STATE, NIGERIA - JIDDA, Kafayah Adeola (Ilorin Journal of Education, 2023)
This study examined attitude towards modern contraceptives as well as differences in attitude of single women towards modern contraceptives based on religion and ethnicity. A descriptive research design of the survey type was used. Population comprised all female final year undergraduates in four Universities in Kwara State from which 1988 respondents were selected through a multistage technique. Structured questionnaire, validated by three experts, with a reliability of 0.76, which was determined through test re-test method was used to elicit responses from the respondents. Percentages, t-test and Analysis of Variance were used for research question and hypotheses set at 0.05 level of significance. The findings revealed that Single women had positive attitude towards modern contraceptive, however differences existed based on religion and ethnicity. Therefore, the study recommends that contraceptive misinformation should be dispelled among single women especially Christian Single women and those of Hausa and Igbo ethnicity to promote good attitude.